Supplies costs: an exploratory study with application of measurement model of logistics costs - Ferreira Alves, Ana Paula; Silva Borba, José Vanderlei; Tavares dos Santos, Gilberto; Gibbon, Artur Roberto (Revista de Administração da UFSM, 2013)
One of the main reasons for the difficulty in adopting an integrated method of calculation of logistics costs is still a lack of adequate information about costs. The management of the supply chain and identify its costs can provide information for their managers, with regard to decision making, generating competitive advantage. Some models of calculating logistics costs are proposed by Uelze (1974), Dias (1996), Goldratt (2002), Christopher (2007), Castiglioni (2009) and Borba & Gibbon (2009), with little disclosure of the results. In this context, this study aims to evaluate the costs of supplies, applying a measurement model of logistics costs. Methodologically, the study characterized as exploratory. The model applied pointed, in original condition, that about R$ 2.5 million were being applied in the process of management of supplies, with replacement costs and storage imbalance. Upgrading the company's data, it is possible obtain a 52% reduction in costs to replace and store supplies. Thus, the cost model applied to logistical supplies showed feasibility of implementation, as well as providing information to assist in management and decision-making in logistics supply.